Pengaruh Kinerja Manajemen Terhadap Kinara Keuangan PT. Industri Karet Deli Periode 2009 - 2021 - Niarita Bukit; Susan Grace Nainggolan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
To find out how much influence Management Performance has on Financial Performance at PT. Deli Rubber Industry, so this research really needs to be done. The method used is explanatory research. While the data analysis technique uses statistical analysis by testing regression, correlation, determination and hypothesis testing. The results of this study are in the form of management performance variables which obtain an average value of 3.81%. The Financial Performance variable is obtained from an average value of 3.91% while Management Performance has a positive and significant effect on Financial Performance with a regression equation Y = 13,1987,981X, and a correlation coefficient value of 0.667 or has a strong relationship with determination value of 44.5%. The hypothesis test obtained a significance of 0.000 <0.05.